The role of biomechanical anatomical modeling via computed tomography for identification of restrictive allograft syndrome. Issue 8 (25th July 2017) - Horie, Miho; Saito, Tomohito; Moseley, Joanne; D'Errico, Luigia; Salazar, Pascal; Nakajima, Daisuke; Brock, Kristy; Yasufuku, Kazuhiro; Binnie, Matthew; Keshavjee, Shaf; Paul, Narinder
Abstract: Chronic lung allograft dysfunction (CLAD) reduces long‐term graft survival. It is important to distinguish CLAD subtypes: bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS) as RAS has a worse prognosis and accurate subtyping could facilitate targeted treatments. However, the current diagnosis of CLAD subtypes is based on pulmonary function test (PFT) results that reflect global estimates of lung function; anatomical modeling based on computed tomography (CT) has the potential to provide detailed analysis of global and regional lung function. The purpose of this study is to evaluate the utility of CT‐based anatomical modeling for the identification of RAS. This retrospective study included 51 patients (CLAD: 17 BOS and 17 RAS, control: 17 No‐CLAD). CT data were assessed using a biomechanical model‐based platform (MORFEUS) to characterize changes in lung deformation between baseline and disease onset. Lung deformation demonstrated high sensitivity and specificity (>80%) in differentiating RAS from BOS ( P <.0001) and No‐CLAD ( P <.0001). There were matching radiological reading and inward deformation abnormalities in 79% of lung sections in patients with RAS. Anatomical modeling is complementary to conventional assessment in the diagnosis of RAS and potentially provides quantitative data that can help in the characterization and detailed assessment of heterogeneous lung parenchymal disease.